Blue Energy: Polymeric Nano‐Blue‐Energy Generator Based on Anion‐Selective Ionomers with 3D Pores and pH‐Driving Gating (Adv. Energy Mater. 44/2020). Issue 44 (24th November 2020) - Zhu, Xuanbo; Zhong, Jundong; Hao, Junran; Wang, Yuzhang; Zhou, Jiajia; Liao, Jingwen; Dong, Yujie; Pang, Jinhui; Zhang, Haibo; Wang, Zizhun; Zhang, Wei; Zheng, Weitao; et al.
Abstract : In article 2001552 by Yahong Zhou and co‐workers fabricate a series of 3D porous membranes based on an amphiphilic ionomer that is composed of both hydrophobic side chains and hydrophilic main chain structures. The controllable adjustment of the pore structure can be realized by designing the polymer molecular structure. The membranes show excellent ionic transmembrane properties and can work as nano‐blue energy generators.